A Note on Schooling and Wage Inequality in the Public and Private Sector - Patrinos, Harry Anthony; Ridao-Cano, Cristobal; Sakellariou, Chris (2012)
The few studies that have examined the wage impact of education across the earning distribution have focused on high-income countries and show education to be more profitable at the top of the distribution. The implication is that education may increase inequality. Extending the analysis to 16 East Asian and Latin American countries, in Latin America we observe a pattern similar to that of Europe/North America (increasing wage effects), while in East Asia the wage effects are predominantly decreasing by earnings quantile. However, once the analysis is performed separately for the public and the private sector, it is revealed that the strongly decreasing impact of schooling on earnings in the public sectors of East Asian countries is responsible for the overall observed decreasing pattern, while the impact of schooling on earnings in the private sectors of these countries is non-decreasing.